THE INFLUENCE OF DIGITALIZATION OF BANKING SERVICES ON OPERATIONAL EFFICIENCY AND CUSTOMER SATISFACTION IN INDONESIA - Akbar Tanjung; Muhamad David Handoko Rivolsyah (Jurnal Intelek Insan Cendikia, 2024)
This study aims to analyze the impact of digitalization in banking services on operational efficiency and customer satisfaction in Indonesia. The research method used is a quantitative approach with data collection through surveys involving 300 customer respondents from various banks in Indonesia. The obtained data were analyzed using multiple regression techniques to determine the relationship between service digitalization, operational efficiency, and customer satisfaction. The results indicate that digitalization of banking services significantly enhances operational efficiency by reducing transaction time and costs. Additionally, digitalization has proven to increase customer satisfaction by providing faster, safer, and more accessible services. The study finds that the adoption of technologies such as mobile banking, internet banking, and more advanced ATMs has helped Indonesian banks serve customers more effectively and efficiently. Digitalization also reduces bank queues, speeds up the verification process, and gives customers greater control over their transactions. The conclusion of this study is that digitalization of banking services has a significant positive impact on operational efficiency and customer satisfaction. Banks in Indonesia are advised to continue developing and implementing digital technologies in their operations to improve performance and competitiveness in the market. Moreover, it is important for banks to continually innovate and adapt to technological advancements to meet the ever-increasing customer expectations. Therefore, digitalization is not only a tool to enhance efficiency but also a strategy to retain and attract new customers.